The Implications of Mental Health and Trauma in Interstitial Cystitis - Tyler R. Bendrick; Graison L. Sitenga; Cameron Booth; Matthew P. Sacco; Christine Erie; Danyon J. Anderson; Alan D. Kaye; Ivan Urits (Health Psychology Research)
This review aims to assess the relationship between interstitial cystitis (IC) and significant traumatic events or PTSD. It was shown that there is a strong correlation between past trauma and the development of interstitial cystitis, as well as a much higher incidence of PTSD in patients diagnosed with IC. It was also established that for individuals with early traumatic experiences, the more likely the development of IC later in life, and with more severe symptoms and adverse effects on quality of life. We describe three distinct hypotheses for the possible physiologic mechanism for development of IC with relation to mental health and trauma, although definitive evidence in this area is still lacking, which poses interesting avenues for further research. This review also revealed an apparent lack of, and need for, trauma informed care and screening for PTSD in patients diagnosed with IC or other chronic pain syndromes.